Little Between-Region and Between-Country Variance When People Form Impressions of Others. (December 2021) - Hester, Neil; Xie, Sally Y.; Hehman, Eric
To what extent are perceivers' first impressions of other individuals dictated by cultural background rather than personal idiosyncrasies? To address this question, we analyzed a globally diverse data set containing 11, 481 adult participants' ratings of 120 targets across 45 countries (2, 597, 624 total ratings). Across ratings of 13 traits, we found that perceivers' idiosyncratic differences accounted for approximately 29% of variance and impressions on their own and approximately 16% in conjunction with target characteristics. However, country- and region-level differences, here a proxy for culture, accounted for 3.2% on average (i.e., both alone and in conjunction with target characteristics). We replicated this pattern of effects in a preregistered analysis on an entirely novel data set containing 7, 007 participants' ratings of 100 targets across 41 countries (24, 886 total ratings). Together, these results suggest that perceivers' impressions of other people are largely dictated by their individual characteristics and local environment rather than their cultural background.